2019
DOI: 10.1109/access.2019.2938633
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Nonconvex Denoising and Unmixing for Hyperspectral Imaging

Abstract: Sparse hyperspectral unmixing aims at finding the sparse fractional abundance vector of a spectral signature present in a mixed pixel. However, there are several types of noise present in the hyperspectral images. These are called mixed noise including stripes, impulse noise and Gaussian noise which deteriorate the performance of sparse unmixing algorithms. In this study, we simultaneously unmix and denoise the hyperspectral image in a unified framework in the presence of mixed noise. In the denoising step, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The combination of unmixing and denoising has been treated in some recent studies. Several research works [35,39,40] developed specific methods that could cope with noise and perform denoising and unmixing simultaneously. In [32][33][34], it was shown that denoising may help to boost the endmember extraction and the unmixing performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of unmixing and denoising has been treated in some recent studies. Several research works [35,39,40] developed specific methods that could cope with noise and perform denoising and unmixing simultaneously. In [32][33][34], it was shown that denoising may help to boost the endmember extraction and the unmixing performance.…”
Section: Discussionmentioning
confidence: 99%
“…Some algorithms were developed to perform denoising and unmixing jointly in a unified framework, with the purpose of improving both. Both in [39,40], sparse representation frameworks were developed, where denoising and unmixing acted as constraints of each other. In most of the aforementioned studies, the performed experiments were small scale and rather anecdotal in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some techniques extract endmembers from class averages defined by ground truth information [83] or from a library of endmembers [84]. Some methods were developed for performing the denoising and unmixing in a unified framework for boosting the performance of each other [85], [86]. Recently, Block-Gaussian-Mixture Priors have been proposed for both hyperspectral denoising and inpainting [87].…”
Section: A Conventional Techniquesmentioning
confidence: 99%
“…Ince et. al propose a coupled unmixing and denoising method [17] to enhance the unmixing performance. Joint-sparse blocks and low-rank unmixing (JSpBLRU) [18] divides the abundance matrix into blocks and solves a joint-sparse regression problem to enhance the sparsity of each block.…”
Section: Introductionmentioning
confidence: 99%